Properties of natural hydroxyapatite prepared by pressureless sintering using different temperatures and holding times - Nuradeen Idris; Bashar Dan-Asabe; Semiyou A. Osseni; Kazeem O. Rabiu; Adetunji R. Sowunmi; Naresh D. Bansod; Frantisek Lukac; Stefan Csaki; David O. Obada (Next Nanotechnology)
The sintering behavior of hydroxyapatite (HAp) particles prepared via pressureless sintering was investigated. The powders were subjected to different sintering temperatures of 900°C and 1000°C for 2, 4, and 6 hours (hr). The sintered HAp powders were analyzed for phase stability, density, Vickers hardness, fracture toughness, brittleness index, and in vitro biological properties. XRD analysis indicated HAp as the dominant phase in all samples. Rietveld refinement quantified the weight percent (wt.%) of HAp to be equal to or more than 97 % in all samples. Scanning electron microscopy (SEM) analyses revealed larger and flattened particle shapes for HAp sintered at 1000°C and this influenced the mechanical properties of the samples. The density of the HAp samples was close to the theoretical density of HAp. Samples sintered with 4-hr holding times displayed greater stability in physiological fluids. In vitro degradation tests in phosphate buffer saline (PBS) under physiological conditions revealed minimal weight loss and stable pH levels over 14 days. This indicates the scaffolds’ potential for long-term physiological stability. Overall, samples sintered at 900°C may be further investigated to enhance their significance in biomedical applications.